Cavern Whisperers Unveiled: Yemen's Inaugural Speleomycobiome Baseline Across Arid Extremes and Zonation Gradients in Zahzah Cave, Amran - Al-Jobory, Hala J. (PSM Microbiology, 2025)
Cave ecosystems constitute paradigmatic oligotrophic refugia where fungal mycobiomes manifest pronounced zonation along light-nutrient gradients. This inaugural systematic inventory documents cultivable microfungi from Zahzah Cave, Yemen—a hyper-arid karst system absent from speleomycological records. Across 30 rigorously sampled matrices (soil n=12, rock n=10, air n=8) spanning entrance-twilight-dark transects, 78 morphotypes (33 genera) emerged, overwhelmingly dominated by Aspergillus (20 spp., 42%) and Penicillium (14 spp., 22%) consortia (>64% relative abundance across substrates). Microclimatic forcings—inward cooling (16.1?9.5°C), escalating lithic moisture (0?20.3%), and ventilation attenuation—drove substrate-specific guilds and diversity attrition: twilight soil apices (395×10³ CFU g?¹, S=46, H?=3.45, ?=0.11) versus dark minima (127×10³ CFU g?¹, S=31, H?=2.76); airborne Cladosporium hegemony (27-29%, 246?99 CFU m?³); edaphic Trichoderma, lithobiontic Trichophyton/Isaria partitioning. Yemen's seminal integrated cave mycology baseline unveils hyper-arid dynamics—Eurotiales supremacy—divergent from temperate/mesic archetypes, catalyzing phylogenomic and extremozyme interrogation of substrate specialists.